An Infidel Discourse in Kebumen Wayang Golek Performance - I Nyoman Murtana (International Journal of Advanced Science and Technology, 2020)
Rod Puppets (Wayang Golek) performance of Menak Malebari story is a repertoire that discusses the spread of Islamic teachings.